An Archaeological Assessment of Fisheries in Vava'u, Tonga. - Densmore, Nadia (My University, 2010)
Archaeological explorations of South Pacific Islands tend to focus on identifying the presence of a distinct dentate stamped pottery style coined "Lapita Ceramics". Studies concerning the subsistence strategies of Lapita settlers tend to be localized to single islands or archipelagos. An examination of archaeological fish remains can provide information concerning the kinds of fish being harvested, the diversity of the fishery, the technology used for harvest, and the relative importance of fish to the overall subsistence economy. Subsistence research in the South Pacific is predominantly centered on the marine environment and Lapita interactions with local marine resources. Identification of fish remains and analysis of the abundances of fish resources on several islands has led to a generalization of Lapita subsistence practices as dominated by reef resources. An analysis of fish remains at four Lapita sites (Falevai, 'Otea, Ofu, and Vuna), in Vava'u Tonga indicates settlers had a complex and diverse relationship with marine environments, and demonstrates that Vava'u fisheries are characterized by the casual harvest of large bodied fish. In addition to a characterization of Vava'u fisheries, a critical comparison of the fishing practices of Tongatapu, Ha'apai and Vava'u highlights the range of subsistence practices employed by the Lapita and defies the imposition of generalized subsistence models on Lapita settlers.
Keywords: Anthropology; Anthropology